The Influence Of Corporate Image, Service Quality and E-Banking on Customer Loyalty at PT Bank Mestika Dharma, TBK KPO Medan - Erick; Hendry; Canny; Kelvin (Jurnal Mantik, 2021)
The research objective was to test and analyze Company Image, Service Quality and E-Banking on Customer Loyalty at PT Bank Mestika Dharma, Tbk KPO Medan. The population in this study amounted to 280 customers and the study sample was 165 customers. The results of the calculation of the partial hypothesis testing, corporate image has a positive and significant effect on customer loyalty at PT Bank Mestika Dharma, Tbk KPO Medan. Partially Service Quality has a positive and significant effect on Customer Loyalty at PT Bank Mestika Dharma, Tbk KPO Medan. Partially E-Banking has a positive and significant effect on Customer Loyalty at PT Bank Mestika Dharma, Tbk KPO Medan. Simultaneously Corporate Image.